2016
DOI: 10.1016/j.aogh.2016.04.523
|View full text |Cite
|
Sign up to set email alerts
|

Do maternal knowledge and attitudes towards childhood immunizations in rural Uganda correlate with complete childhood vaccination?

Abstract: Improving childhood vaccination coverage and timeliness is a key health policy objective in many developing countries such as Uganda. Of the many factors known to influence uptake of childhood immunizations in under resourced settings, parents' understanding and perception of childhood immunizations has largely been overlooked. The aims of this study were to survey mothers' knowledge and attitudes towards childhood immunizations and then determine if these variables correlate with the timely vaccination covera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
18
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 19 publications
6
18
1
2
Order By: Relevance
“…Some previous studies heavily highlight maternal education because the mothers usually take care of children and spend more time to be with their children in daily basis. The role of mothers was considered more important than fathers (Hudhah & Hidajah, 2017;Rachman, Handayani, & Ridwan, 2015;Vonasek et al, 2016) Some other studies in Indonesia revealed the contrast results. The role of fathers in some communities was more important than mothers, even when the education and income level of the mothers were better (Herliana & Douiri, 2017;Holipah, Maharani, & Kuroda, 2018;Jayanti, Sulaeman, & Pamungkasari, 2017).…”
Section: The Characteristics Of Respondentsmentioning
confidence: 99%
“…Some previous studies heavily highlight maternal education because the mothers usually take care of children and spend more time to be with their children in daily basis. The role of mothers was considered more important than fathers (Hudhah & Hidajah, 2017;Rachman, Handayani, & Ridwan, 2015;Vonasek et al, 2016) Some other studies in Indonesia revealed the contrast results. The role of fathers in some communities was more important than mothers, even when the education and income level of the mothers were better (Herliana & Douiri, 2017;Holipah, Maharani, & Kuroda, 2018;Jayanti, Sulaeman, & Pamungkasari, 2017).…”
Section: The Characteristics Of Respondentsmentioning
confidence: 99%
“…Overall, there is a good understanding of vaccine schedules and the benefits of vaccinations in limiting illness, disability and death among residents of these islands and fishing communities, as reported in the Northern part of Uganda [13]. However, this assessment demonstrates that barriers to accessing vital health services, including immunisations prevail in fishing and island communities.…”
Section: Discussionmentioning
confidence: 90%
“…Mothers who knew the bene ts of childhood immunization were six times as likely to have their children fully immunized compared with their counterpart [29,30]. Having expectation towards the protection that follows childhood immunization signi cantly in uence childhood immunization [52]. Likewise, Knowing the seriousness of VPDs was also found to be a predictor for non-compliance [41].…”
Section: Maternal Outcome Expectationsmentioning
confidence: 89%
“…With regards to maternal outcome expectation, three studies reported knowledge on bene t of childhood immunization uptake [29,30,52] and one study revealed severity of VPDs [41]. For environmental factors, two studies reported religious belief [40,64].…”
Section: Modi Able Factorsmentioning
confidence: 99%